2010
DOI: 10.1007/s12571-010-0078-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid gains in food security from new maize varieties for complex hillside environments through farmer participation

Abstract: This is a follow-up study of two previous papers in this series in which we discussed the effectiveness of participatory varietal selection (PVS) and community-based seed production (CBSP). In this paper we present from survey results the impact of new, improved varieties on food security of farmers who had previously participated in PVS or CBSP, or both. A total of 230 households from eight locations, representing different social classes (A, B, C), castes (Dalit, Janajati, BCTN; referring to Bahun, Chhetry, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Pandit et al (2010) also agreed with the finding that seed dissemination through this approach was rapid. Tiwari et al (2010) and Thapa et al (2009) highlighted the power of evaluating new varieties under farmers' management to greatly enhance cultivar identification based on farmers' choice, a process that leads to the selection of varieties with yield stability and ultimately provides additional benefits to farmers.…”
Section: Effectiveness Of Pvs Approachmentioning
confidence: 99%
“…Pandit et al (2010) also agreed with the finding that seed dissemination through this approach was rapid. Tiwari et al (2010) and Thapa et al (2009) highlighted the power of evaluating new varieties under farmers' management to greatly enhance cultivar identification based on farmers' choice, a process that leads to the selection of varieties with yield stability and ultimately provides additional benefits to farmers.…”
Section: Effectiveness Of Pvs Approachmentioning
confidence: 99%
“…Lilja and Erenstein (2002) describe how evidence from these approaches is important for strategic decision makers in overcoming resistance by national systems to adopt participatory research methods. Tiwari et al (2010) reported that PVS can greatly contribute to improved food security by addressing the issues of social exclusion and discrimination based on gender, ethnicity and caste and that it can have important institutional impacts in making the research and development process more inclusive and demand-driven.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a participatory seed selection and multiplication project in Nepal using new varieties of crops increased yields by about 45% and improved stability in household food access. A special feature of this project was that it reached poor and female-headed households and lower-caste households much better than the regular extension services (Tiwari et al 2010). Likewise, farmers in PRC, India, and Pakistan were reported to have used less pesticides and better practices after a training program on the integrated pest management of cotton.…”
Section: B Extension Methodsmentioning
confidence: 98%